2010
DOI: 10.1002/j.1662-6370.2010.tb00435.x
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing the Vote: Individual, Communal, and Cantonal Sources of Voting Behavior in Switzerland

Abstract: This article considers individual, communal, and cantonal sources of voting behavior in the 2007 National Council elections in Switzerland. Using hierarchical linear models, it is shown how the vote propensity for the five main parties (CVP, FDP, Greens, SP, and SVP) varies across individuals, communes, and cantons. Key explanatory factors at each of these levels are explored, as well as cross‐party differences in the effects of these factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Prior evidence for the effects of age are mixed, however. While age effects are small, some have found a positive (e.g., Fitzgerald & Lawrence, ; Fontana et al, ), others a negative (Arzheimer, ; Lucassen & Lubbers, ; Lubbers & Scheepers, ; Werts et al, ), and yet others no relationship (Arzheimer & Carter, ; Oesch, ; Steenbergen, ; Stockemer, ) with radical right voting. Finally, having a migration background may also relate to lower support for SVP.…”
Section: Radical Right Voting In Switzerland: Summary Of Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior evidence for the effects of age are mixed, however. While age effects are small, some have found a positive (e.g., Fitzgerald & Lawrence, ; Fontana et al, ), others a negative (Arzheimer, ; Lucassen & Lubbers, ; Lubbers & Scheepers, ; Werts et al, ), and yet others no relationship (Arzheimer & Carter, ; Oesch, ; Steenbergen, ; Stockemer, ) with radical right voting. Finally, having a migration background may also relate to lower support for SVP.…”
Section: Radical Right Voting In Switzerland: Summary Of Predictionsmentioning
confidence: 99%
“…Sociodemographic factors known to influence radical right‐wing voting (education and perceived financial situation, gender, age, and migration background) are accounted for prior to testing our main hypotheses. It is likely that members of low‐status categories—low education or struggling to make ends meet—experience immigrants as more threatening than others and may thus be more inclined to vote for the SVP (Steenbergen, ; see also Arzheimer & Carter, ; Oesch & Renwald, ). Also, men frequently vote for the radical right more than women (Fontana, Sidler, & Hardmeier, ).…”
Section: Radical Right Voting In Switzerland: Summary Of Predictionsmentioning
confidence: 99%
“…We have demonstrated that political messages espoused by a party that owns the issue have the potential to influence voters’ preferences. However, people are “limited information processors” (Lau and Redlawsk : 23); they are biased in how they process information (e.g., Fiske and Taylor ; Kunda ; Steenbergen ; Taber and Lodge ; Zaller ). Thus, the availability of a particular campaign message does not imply its automatic acceptance.…”
Section: Hypothesesmentioning
confidence: 99%
“…Studentsat least in the higher age groups of the samplecan be expected to have basic knowledge in the respective foreign language. We opted for using the language information in subsequent analysis because, traditionally, substantial regional differences exist in Switzerland when it comes to attitudes and certain forms of behaviors, such as voting (Steenbergen, 2010). Some of these differences fall along language lines -a phenomenon often described with the humorous term "Röstigraben" (Rösti ditch) (Brügger, Lalive, & Zweimüller, 2009).…”
Section: Questionnaire and Measurementmentioning
confidence: 99%